Qatar : Staff Report for the 2015 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2015)
This 2015 Article IV Consultation highlights that Qatar is implementing an ambitious diversification strategy, while retaining its systemic role in the global natural gas market. Qatar accounts for one-third of global liquefied natural gas trade and has emerged as an important global financial investor, labor importer, and donor. The authorities are executing a large public infrastructure program to advance economic diversification and prepare for the FIFA 2022 World Cup. The economy has maintained strong growth momentum so far despite the large drop in oil prices since summer 2014. The short-term growth outlook is positive, but lower oil prices will lead to a substantial deterioration of the fiscal and external balances.